Fungsi Kalbu (al-Qalb) menurut Tafsir Al-Marāghī - Awandano, Cikal; Nasution, Muhammad Roihan (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study aims to analyze the meaning and function of qalb (heart) from the perspective of Ahmad Mustafa al-Marāghī as presented in Tafsīr al-Marāghī, focusing on verses that highlight the role of the heart in understanding divine truth, particularly Q.S. al-Ḥajj: 46, Q.S. Qāf: 37, and Q.S. al-A‘rāf: 179. The study employs a qualitative research method with a library research approach, utilizing descriptive and interpretative analysis of the tafsīr text and relevant supporting literature. The findings reveal that al-Marāghī interprets the qalb not merely as a physical organ but as the center of spiritual consciousness that plays a crucial role in the process of thinking, understanding, and responding to divine truth. According to al-Marāghī, the qalb serves as a moral and epistemological instrument that bridges reason and faith, forming the foundation for human awareness, belief, and ethical behavior. This study emphasizes that the success of humans in attaining divine guidance and wisdom greatly depends on the purity and sensitivity of their conscience. Thus, the results of this study are expected to enrich the conceptual understanding of qalb in the corpus of Qur’anic exegesis and contribute to the development of Islamic ethics and spirituality in the modern era.